Formulasi dan Uji Mutu Fisik Sediaan Lulur (Scrub) Ekstrak Kulit Jeruk Nipis (Citrus Aurantifolia) dan Beras Putih (Oryza Sativa): Penelitian - Alfi Risna Fadilla; Kusumaningtyas Siwi A; Tatiana Siska Wardani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Body scrub is one of the cosmetic pharmaceutical products that functions to smooth the skin by removing dead skin cells. White rice (Oryza sativa) is used as abrasive material in making body scrubs. Lime peel contains more than 60% flavonoids and around 170 different types of phytonutrient compounds. Flavonoids are the main group of polyphenol compounds that have antioxidant properties. This study aims to identify the content of secondary metabolites in lime peel extract, test the physical quality standards of the body scrub, and determine the best body scrub formulation. The method used in this study is a laboratory experimental method. The extraction process was carried out using maceration techniques using 70% ethanol solvent. Furthermore, a phytochemical screening test was carried out to identify the content of active compounds, as well as physical testing on body scrub preparations with three different extract concentrations (2%, 3%, and 4%). In addition, a hedonic test was carried out to assess the level of preference and an irritation test to ensure product safety. Data analysis was carried out using One Way ANOVA to see the differences between formulas, and a Dependent T-test to test the level of preference for body scrub preparations. The results of the observation showed that lime peel (Citrus aurantifolia) contains various secondary metabolites, including flavonoids, alkaloids, tannins, saponins, terpenoids, and antioxidant compounds.